Pola Penggunaan Obat Pada Masa Pandemi Covid-19: Studi Kasus di Rumah Sakit Umum Pusat Persahabatan - Fitri Nurhayati; Dendhi Bagus Andriyanto; Fadhila Putri; Rara Merinda Puspitasari (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
The COVID-19 pandemic condition has encouraged healthcare practitioners to adapt and constantly work to meet the needs of those who require healthcare, including medication supply. This study aims to provide the drug use patterns prior to and throughout the COVID-19 pandemic. This retrospective descriptive study analyzed the drug use patterns of 10 fast-moving drugs obtained through purposive sampling, as well as all medications listed in COVID-19 guideline therapy at Persahabatan general hospital. The drug use data was derived from the quarterly data from 2019 through the second quarter of 2021. The result showed that there was an increase and variation in the sampled drug usage. The top-ranking classes that have shown an upward trend during the COVID-19 pandemic were Vitamin C 500 mg tablet, Vitamin C 200 mg injection, and Vitamin D3 5000 UI tablet. Meanwhile, non-COVID-19 medicines with reduced use include Cefotaxime 1 g, Cefixime 200 mg, and Docetaxel 20 mg. Therefore, it is necessary to analyze the drug utilization continuously and as frequently as feasible throughout the pandemic and plan in stages. Forecasting demand for medicines is essential for an effective medicinessupply chain, in particular in a pandemic context to avoid shortages or overstock.